2004
DOI: 10.1080/10473289.2004.10470881
|View full text |Cite
|
Sign up to set email alerts
|

Selective Catalytic Oxidation of Ammonia over Copper-Cerium Composite Catalyst

Abstract: This work considers the oxidation of ammonia (NH 3 ) by selective catalytic oxidation (SCO) over a copper (Cu)-cerium (Ce) composite catalyst at temperatures between 150 and 400°C. A Cu-Ce composite catalyst was prepared by coprecipitation of copper nitrate and cerium nitrate at various molar concentrations. This study also considers how the concentration of influent NH 3 (500 -1000 ppm), the space velocity (72,000 -110,000 hr Ϫ1 ), the relative humidity (12-18%) and the concentration of oxygen (4 -20%) affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…Copper and cerium are known to form Cu-Ce redox couples (Cu 2+ -O-Ce 4+ ) that, during the oxidation processes, are responsible for the activation of lattice oxygen. A similar synergistic effect was previously reported by Wang et al [ 49 ], Lou et al [ 50 ] and Gang et al [ 31 ].…”
Section: Discussionsupporting
confidence: 90%
“…Copper and cerium are known to form Cu-Ce redox couples (Cu 2+ -O-Ce 4+ ) that, during the oxidation processes, are responsible for the activation of lattice oxygen. A similar synergistic effect was previously reported by Wang et al [ 49 ], Lou et al [ 50 ] and Gang et al [ 31 ].…”
Section: Discussionsupporting
confidence: 90%
“…According to the mechanisms of ammonia oxidation described in the literature the most probable mechanisms for Cu-Mg-Fe mixed metal oxides is the internal selective ammonia oxidation (i-SCR) that include oxidation of part of NH 3 to NO and further NO reduction by NH 3 to N 2 [13,16,17]. Because of that, possible improvement of Cu-Mg-Fe catalysts activity could be reached by the modification of their surface by other metals (e.g., noble metals, [16][17][18][19]59]) that are responsible for selective oxidation of ammonia to NO [60] and ensuring the accessibility of active species by structural promoters, e.g., aluminum [14,21,57,61].…”
Section: Catalytic Studiesmentioning
confidence: 99%
“…NH3-SCO over the catalysts prepared via different techniques followed the i-SCR mechanism (with the -NHx and -HNO intermediates, Figure 7a) [98]. Lou et al [99] have reported nearly complete NH3 conversion at temperatures as high as 400 °C with an overall N2 selectivity varying from 19 to 82% over Cu-Ce mixed oxides prepared by coprecipitation with an optimum at n(Cu)/n(Ce) = 6/4 (among 6-9/1-4). Afterward, the CuO-CeO2 catalysts prepared by a surfactant-templated method exhibited full NH3 conversion below 300 °C with more than 90% N2 selectivity [100].…”
Section: Other Metal Oxidesmentioning
confidence: 99%